Laboratory investigations to assess the feasibility of employing a novel mixed-in-place offshore pile in calcareous deposits. (2nd January 2020) - Doherty, Paul; Spagnoli, Giovanni; Doherty, Mark
ABSTRACT: Calcareous sands are typical of warmer seas and are encountered in several high growth locations around the world. Despite having high frictional resistance with friction angles exceeding those of siliceous sands, the in situ behaviour is characterised by particle damage and extreme contraction at high confining stresses. This behaviour results in very low values of skin friction for driven piles in calcareous deposits, where the contraction dominates the pile response. The MIxed Drilled Offshore Steel (MIDOS) pile is a novel mixed-in-place technology which has many advantages over driven steel piles and conventional drilled-and-grouted (D&G) piles. The MIDOS is based on the deep-mixing technology normally used as an onshore ground improvement technique. The mechanical technology and in situ pile performance were successfully demonstrated during an in situ test in silica sand. A laboratory based study was undertaken to assess the MIDOS performance in calcareous sand. Geotechnical tests, grout tests and steel–grout pull out tests were performed to assess the sands and to model the behaviour at the interface of the steel reinforcement and the grout body. These preliminary results demonstrate that the frictional shaft resistance at the pile–soil interface is comparable for both silica and calcareous sands, and as there is no stress relief or contraction during the installation process, the geotechnical performance of the MIDOS pile is deemed comparable for both soil types tested.